LANGUAGE AS A SOCIAL PHENOMENON (British Journal of Global Ecology and Sustainable Development, 2025)
This topic forms an idea of the social character of language and different points of view on its origin. It also reveals the role of language in the development of society and the degree of influence of society on language: social and territorial differentiation of language, functional styles, etc.